Osteopetrosis with Micro-lacunar Resorption due to Defective Integrin Organization - Blair, Harry C (2009)
We used in vitro differentiation of monocytes to characterize the cellular defect in a type of osteopetrosis with minimally functional osteoclasts, where defects associated with common causes of osteopetrosis were excluded by gene sequencing. Monocytes from blood of a 28 year old subject were differentiated in media with RANKL and CSF-1. Cell fusion, acid compartments within cells, and TRAP activity were normal. However, the osteoclasts made abnormally small pits on dentine. Phalloidin labeling showed that the cell attachments lacked the peripheral ring structure that supports lacunar resorption. Instead, the osteoclasts had clusters of podosomes near the center of cell attachments. Antibody to the αvβ3 integrin pair or to the C-terminal of β3 did not label podosomes, but antibody to αv labeled them. Western blots using antibody to the N-terminal of β3 showed a protein of reduced size. Integrins β1 and β5 were upregulated, but, in contrast to observations in β3 defects, α2 was not increased. The rho GTP exchange protein Vav3, a key attachment organizing protein, did not localize normally with peripheral attachment structures. Vav3 forms of 70 kD and 90 kD were identified on Western blots. However, the proteins β3 integrin, Vav3, Plekhm1 and Src, implicated in attachment defects, had normal exon sequences. In this new type of osteopetrosis, the integrin organizing complex is dysfunctional, and at least two attachment proteins may be partially degraded.